Comportamiento de los depósitos y créditos del sistema financiero no bancario de las regiones Loreto, San Martín y Ucayali periodo 2017 - 2021 - Chagas Tenazoa, Percy Jhonatan (2023)
Non-banking institutions are part of the Financial System, the present work behavior of deposits and credits of the non-banking Financial System of the Loreto, San Martín and Ucayali regions, period 2017 - 2021 aims to Evaluate the behavior of deposits and credits of the non-banking financial system of the Loreto, San Martín and Ucayali regions, period 2017-2021, the research is of an applied type with a quantitative approach at a descriptive level and a non-experimental design. The results show that the San Martín region is the one with the highest balance of deposits, ending the period with 337 million soles, followed by the Loreto region with 253 million soles and the Ucayali region ending with 133 million soles; Regarding credits, the San Martín region ended with 955 million soles, followed by the Ucayali region with 565 million soles and the Loreto region closes with 551 million soles. The deposit / credit ratio for the San Martín region in 2021 is 35.29%, for the Loreto region it is 45.92% and for the Ucayali region 23.54%